2020
DOI: 10.5032/jae.2020.02324
|View full text |Cite
|
Sign up to set email alerts
|

Images from the Trenches: A Visual Narrative of the Concerns of Agricultural Education Majors

Richie Roberts,
Kristin S. Stair,
Tyler Granberry

Abstract: This study described how agricultural education majors at Louisiana State University visually represented and narrated their concerns about teaching. To accomplish this, students captured photos during early field experiences (EFEs) and then critically reflected on those experiences through focus group interviews during the Fall 2018 and Fall 2019 academic semesters. As a product of our analysis of data, we offered a visual narrative of students’ concerns through three themes: (1) Blurred Expectations: Represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…The literature in agriculture has also explored the short-term impacts and best practices of study abroad courses (Bunch et al, 2018;Conner et al, 2019;Conner & Roberts, 2015;Dobbins et al, 2019Dobbins et al, , 2020Lamm et al, 2011;O'Malley et al, 2019;Roberts & Edwards, 2016, Roberts et al, 2020a, 2020b. During short-term study abroad courses, existing evidence has demonstrated that students can began to reexamine their lifestyle, beliefs, attitudes, and behaviors (Dobbins et al, 2019(Dobbins et al, , 2020O'Malley et al, 2019;Roberts & Edwards, 2016, Roberts et al, 2020a.…”
Section: Introductionmentioning
confidence: 99%
“…The literature in agriculture has also explored the short-term impacts and best practices of study abroad courses (Bunch et al, 2018;Conner et al, 2019;Conner & Roberts, 2015;Dobbins et al, 2019Dobbins et al, , 2020Lamm et al, 2011;O'Malley et al, 2019;Roberts & Edwards, 2016, Roberts et al, 2020a, 2020b. During short-term study abroad courses, existing evidence has demonstrated that students can began to reexamine their lifestyle, beliefs, attitudes, and behaviors (Dobbins et al, 2019(Dobbins et al, , 2020O'Malley et al, 2019;Roberts & Edwards, 2016, Roberts et al, 2020a.…”
Section: Introductionmentioning
confidence: 99%
“…As such, we recommend that North Carolina AgrAbility provide tailored training and professional development for staff regarding how to best communicate with caregivers as well as farmers with a disability. We also recommend that North Carolina AgrAbility embed listening sessions into professional development opportunities so that caregivers can be given a space to articulate their concerns and staff can respond accordingly (Roberts et al, 2020a). Finally, additional research should seek to understand how caregivers could better navigate barriers to become empowered through the North Carolina AgrAbility Project and better sustain the agricultural pipeline for future generations (Alston et al, 2019(Alston et al, , 2020.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%
“…Perhaps to make these power dynamics more accessible for students, faculty could embed approaches that seek to illuminate norms and traditions that are often less tangible and difficult for students to grasp (Hartman & Kiely, 2014). As such, we recommend that visual methodologies be incorporated into study abroad courses so that students can capture issues and problems they may struggle to assign meaning to during the experience (Dobbins et al, 2019(Dobbins et al, , 2020Roberts et al, 2020b). Then, through individual and social reflection of powerful images, the students can more deeply ponder the lived experiences of individuals who lack power in different social systems and begin to gain a greater sense of empathy (O'Malley et al, 2019).…”
Section: Purpose and Objectivesmentioning
confidence: 99%
“…Therefore, graduates should be culturally competent and equipped with the ability to address complex problems (Lewis & Gibson, 2008;National Association of State and Land-Grant Colleges [NASULGC], 2004). So far, evidence on study abroad courses in agriculture has documented the motivations and barriers of university agriculture students' participation (Raczkoski et al, 2018;Roberts et al, 2020bRoberts et al, , 2020c. On this point, Raczkoski et al (2018) reported that university agriculture students were largely intrinsically motivated to participate in study abroad courses; however, the perceived cost of the experience and its relative value also influenced their decisions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation